2020
DOI: 10.21203/rs.3.rs-35994/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessing burden, risk factors, and perceived impact of uterine fibroids on women’s lives in rural Haiti: implications for advancing a health equity agenda, a mixed methods study

Abstract: Background Uterine fibroids, the most common cause of gynecologic surgery, have a reported lifetime cumulative incidence of 59% among Black women in the U.S. Uterine fibroids increase mortality, morbidity, and negatively impact the quality of women’s lives. To our knowledge, no study has been published in the literature about fibroids in Haiti. We conducted a mixed methods study to assess the burden and risk factors of uterine fibroids, as well as their effects on women’s quality of life. Methods A convergen… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Oftentimes, African women present late in the course of disease when broids have grown to unmanageable proportions and are causing debilitating health issues, such as severe hemorrhage and grave anemia. Not only that, lacking highly skilled experts, poor quality of services, unaffordable pharmaceutical costs and poor nutritional status together aggravates morbidity and mortality in African countries [29,30]. On this ground, education and increased awareness of the symptoms of uterine broids as well as international collaborations and support such as provide healthcare and transfer skills, medical supplies donation, facilities construction may ameliorate the current situation [29,31].…”
Section: Discussionmentioning
confidence: 99%
“…Oftentimes, African women present late in the course of disease when broids have grown to unmanageable proportions and are causing debilitating health issues, such as severe hemorrhage and grave anemia. Not only that, lacking highly skilled experts, poor quality of services, unaffordable pharmaceutical costs and poor nutritional status together aggravates morbidity and mortality in African countries [29,30]. On this ground, education and increased awareness of the symptoms of uterine broids as well as international collaborations and support such as provide healthcare and transfer skills, medical supplies donation, facilities construction may ameliorate the current situation [29,31].…”
Section: Discussionmentioning
confidence: 99%
“…In a previous report by Millien et al, it was revealed that patients with fibroids may at times refuse surgery for fibroids because of the fear of losing their fertility, the reputation of the hospital and its personnel, the desire to be pregnant before surgery, the lack of income to look for care and peer advice. 11 Millien et al report concluded that “vicious cycle of poverty negatively impacts access to care for uterine fibroids.” 12…”
Section: Discussionmentioning
confidence: 99%
“…11 Millien et al report concluded that "vicious cycle of poverty negatively impacts access to care for uterine fibroids." 12 Ultrasound was the initial screening tool for uterine fibroids because it is non-invasive and cost-effective. 13,14 Ultrasound is easily available even in low-and middleincome settings and can be performed in out-patient basis.…”
Section: Discussionmentioning
confidence: 99%